(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The issues of cleaning grain mixtures from weed seeds and impurities that fall into a heap with the seeds of the main crop during harvesting are considered. The selection of features of grain mixture divisibility, methods and technical means is analyzed, taking into account the input parameters related to the raw materials being processed, as well as the design and operating parameters of grain cleaning machines. It is shown that the most effective separators are gravity separators, in which energy is not spent on the separation process. A method of gravitational separation of grain mixtures by friction under the action of gravity during the movement of particles along a cylindrical curvilinear surface is proposed. The movement of a material particle along the cylindrical surface of a gravity separator is considered. A calculation scheme of particle motion is given, and for various values of the friction coefficient, the dependences of the angular coordinate of the point of separation of the particle from the separator surface and, taking into account this order, the corresponding location of the distribution product receivers are obtained. Graphs of the dependence of the angles α and β on the friction coefficient of the mixture particles along the cylindrical friction surface are constructed. A schematic diagram of a gravity separator with a separating cylindrical friction surface is proposed.